Frações oxidáveis do carbono orgânico total e macrofauna edáfica em sistema de integração lavoura-pecuária - Batista, Itaynara [UNESP]; Correia, Maria Elizabeth Fernandes; Pereira, Marcos Gervasio; Bieluczyk, Wanderlei; Schiavo, Jolimar Antonio; Rouws, Janaína Ribeiro Costa (Sociedade Brasileira de Ciência do Solo, 2014)
The increasing level of land degradation has led to the adoption of agricultural management practices that seek to combine agricultural production and soil conservation. Among these, the practice of Crop-Livestock Integration (CLI) has intensified in West-Central Brazil. In order to assess the long-term effect of the CLI system and seasonality on the community of soil macrofauna and oxidizable fractions of total organic C in croplands and the Cerradão (Brazilian tropical savanna), a study was developed at the Cabeceira Farm in the municipality of Maracaju, State of Mato Grosso do Sul, which measured the effect of CLI on oxidizable fractions of total organic C and soil macrofauna. The CLI system has been used in this area since 2003. The soil was identified as a Latossolo Vermelho (Ferrasol), on flat land. The areas sampled have the following history of use: soybean/corn + brachiaria grass/cotton/oat + pasture/soybean/implantation of pasture/pasture. Sampling was carried out in two seasons, dry and wet. In the dry season, the crops were pasture, corn+brachiaria grass and cotton; in the rainy season there were corn+brachiaria grass, cotton, and soybeans. Thus, the areas in the two evaluation periods were pasture/corn, corn+brachiaria/cotton, cotton/soybeans, and an area of native Cerrado. Sampling was performed at the depths of 0-10, 10-20, and 20-30 cm, and the following determinations were made: analysis of soil macrofauna, particle size fractionation of soil organic matter (SOM), and oxidizable fractions of total organic C. The areas do not have an experimental design as this is an observational study. Data were compared by the Kruskal Wallis test at 5 % probability and through analysis of redundancy. Compartmentalization of SOM can be used to assess the quality of management, with the most sensitive compartments being the F1 and F2 fractions in the assessment of oxidizable fractions. These fractions are more labile in the soil, whereas the F3 and F4 fractions are more recalcitrant. Isoptera (termites) may be acting as a wetting agent of organic matter in the Cerrado area, contributing to higher levels of F3 and F4, compared to F1 and F2, in the dry season. This pattern was only observed in the Cerrado area since in the production areas, Isoptera is controlled by management practices. The lack of these insects in the CLI system may be reducing the stabilization of SOM in the F3 and F4 fractions.

O crescente nível de degradação das terras tem promovido a adoção de manejos agrícolas que busque aliar a produção agropecuária à conservação do solo. Entre esses, a prática da Integração Lavoura-Pecuária (ILP) tem intensificado-se no Centro-Oeste brasileiro. Com o objetivo de avaliar o efeito em longo prazo do sistema ILP e da sazonalidade, sob a comunidade da macrofauna edáfica e das frações oxidáveis do carbono orgânico total (COT) em áreas de cultivo e Cerradão, foi desenvolvido na Fazenda Cabeceira no município de Maracaju, MS, um estudo em que se mensurou a influência da ILP sobre as frações oxidáveis do COT e sobre a macrofauna edáfica. O sistema ILP está sendo utilizado nessa área desde 2003; o solo foi identificado como Latossolo Vermelho, localizado em área de relevo plano. As áreas amostradas possuem o seguinte histórico: soja/milho + braquiária/algodão/ aveia + pastagem/soja/formação da pastagem/pastagem; as amostragens foram realizadas na época seca, em que as culturas presentes eram pasto, milho+braquiária e algodão; e na chuvosa, com milho+braquiária, algodão e soja. Assim, as áreas nas duas épocas de avaliação foram: pasto/milho, milho+braquiária/ algodão, algodão/soja e uma área nativa de Cerradão. A amostragem foi realizada nas profundidades de 0-10, 10-20 e 20-30 cm, sendo feitas as seguintes determinações: análise da macrofauna edáfica, fracionamento granulométrico da matéria orgânica do solo (MOS) e frações oxidáveis do COT. As áreas não apresentavam delineamento experimental, sendo este um estudo de observação. Os dados foram comparados pelo teste de Kruskal Wallis a 5 % e por meio da análise de redundância. A compartimentalização da MOS pode ser utilizada para a avaliação da qualidade do manejo, sendo os compartimentos mais sensíveis as frações F1 e F2 de frações oxidáveis, pois são mais lábeis no solo, já as frações F3 e F4 são as mais recalcitrantes. Isoptera (cupim) pode estar atuando como agente humificador da matéria orgânica na área de Cerradão, contribuindo para maiores teores de F3 e F4, em relação à F1 e F2 na época seca. Esse padrão somente foi verificado na área de Cerradão, visto que nas áreas de produção, Isoptera é controlado pelo manejo. A falta desse inseto no sistema ILP pode estar reduzindo a estabilização da MOS nas frações F3 e F4.
Oxidizable fractions of total organic carbon and soil macrofauna in a crop-livestock integration system
Keywords: matéria orgânica; sazonalidade; manejo; invertebrados; organic matter; seasonality; management; invertebrates